Drug-Related Morbidity and Mortality in Maine: Lost Productivity from 2015 to 2020 - Daley, Angela; Sarker, Prianka; Sigaud, Liam; Sorg, Marcella; Wren, Jamie (Maine Policy Review, 2022)
The authors of this article characterize drug-related morbidity and mortality in Maine between 2015 and 2020, as well as the impact on labor market and nonmarket productivity. We find that prevalence of drug misuse and the number of drug-related deaths have increased across time, and both are lower among females vs males. Drug-related morbidity is concentrated among individuals aged 18–25, while mortality is concentrated among those aged 25–54. Lost productivity has increased across time and is lower among females vs males. In 2019, lost productivity was $271 million (annual) from morbidity and $565 million (lifetime) from mortality. These estimates reflect the lost value to Maine that occurs when individuals cannot fully contribute to the labor market or nonmarket activities. On balance, our study provides important information about the drug epidemic in Maine, which may be helpful to decision makers as they design and evaluate relevant policies and programs.
Keywords: drug; morbidity; mortality; economic impact; productivity; opioids; fentanyl